Schaum's A-Z chemistry - Hunt, J. A. (James Andrew), 1942-; Hunt, J. A., (James Andrew), 1942- (New York : McGraw-Hill, 2003)
Alphabetically arranged entries provide hundreds of definitions and explanations for the basic terms and concepts of chemistry; includes diagrams and charts for quick reference.
Rev. ed. of: The complete A-Z chemistry handbook. 2nd ed. c2000.
Young Adult
Keywords: Chemistry -- Handbooks, manuals, etc; Chemistry -- Examinations -- Study guides; Chemistry -- Handbooks, manuals, etc; Chemistry -- Examinations -- Study guides